Passive Mineral Carbonation of Mg-rich Mine Wastes by Atmospheric CO2. (July 2017) - Beaudoin, Georges; Nowamooz, Ali; Assima, Gnouyaro Palla; Lechat, Karl; Gras, Antoine; Entezari, Ali; Kandji, El Hadji Babacar; Awoh, Akué-Sylvette; Horswill, Micha; Turcotte, Sara; Larachi, Faïçal; Dupuis, Christian; et al.
Abstract: Mg-rich process tailings and waste rocks from mining operations can react spontaneously with atmospheric CO2 to form stable carbonate minerals by exothermic reactions. Over the last decade, we have conducted a number of laboratory and field experiments and surveys on both mine waste rocks and different types of mine tailings from Ni-Cu, chrysotile, and diamond mines. The experiments and surveys cover a wide range of time (10 3 to 10 8 s) and mass (1-10 8 g) scales. Mine waste rich in brucite or chrysotile enhances the mineral carbonation reactions. Water saturation, but more importantly, watering frequency, are highly important to optimize carbonation. Adjusting the chemical composition of the interstitial water to favour Mg dissolution and to prevent passivation of the reaction surfaces is crucial to ensure the progress of the carbonation reactions. Preservation of the permeability structure is also critical to facilitate water and CO2 migration in the rock wastes and tailings. In field experiments, CO2 supply controled by diffusion in the mining waste is slower than the reaction rate which limits the capture of atmospheric CO2 . Industrial implementation of passive mineral carbonation of mine waste by atmospheric CO2 can be optimized using the above parameters.